2021
DOI: 10.3389/fpubh.2021.742378
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Malaria Persistence: A Mixed-Methods Study on the Effectiveness of Malaria Elimination Strategies in South-Central Vietnam

Abstract: Despite the scale-up of vector control, diagnosis and treatment, and health information campaigns, malaria persists in the forested areas of South-Central Vietnam, home to ethnic minority populations. A mixed-methods study using an exploratory sequential design was conducted in 10 Ra-glai villages in Bac Ai district of Ninh Thuan province to examine which social factors limited the effectiveness of the national malaria elimination strategy in the local setting. Territorial arrangements and mobility were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In Myanmar, ITN use was limited by the hard material of ITNs, the limited choice in net size to accommodate variable family sizes and sleeping places, and the inadequate height of the net for people to sit comfortably [ 46 ]. In Vietnam, limited ITN use was linked to hard netting [ 41 ], the design of ITNs that was uncomfortable for users who slept on the floor (without a bed), and limited choices for net size for varied family and house size [ 47 , 48 ]. These studies suggest a more appropriate ITN design and features that are better adapted to climatic conditions, variable family structures and sleeping places could increase the acceptance and appropriate use in minority populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Myanmar, ITN use was limited by the hard material of ITNs, the limited choice in net size to accommodate variable family sizes and sleeping places, and the inadequate height of the net for people to sit comfortably [ 46 ]. In Vietnam, limited ITN use was linked to hard netting [ 41 ], the design of ITNs that was uncomfortable for users who slept on the floor (without a bed), and limited choices for net size for varied family and house size [ 47 , 48 ]. These studies suggest a more appropriate ITN design and features that are better adapted to climatic conditions, variable family structures and sleeping places could increase the acceptance and appropriate use in minority populations.…”
Section: Discussionmentioning
confidence: 99%
“…In Cambodia and Vietnam, researchers reported a major difference between self-reported net use the night before the survey and observed net use at people’s homes [ 33 , 61 ]. Other mixed methods studies in Southeast Asia, including qualitative methods before conducting a survey, resulted in the inclusion of a series of local factors to measure effective bed net use such as mobility between fields and villages, availability and use of intact bed nets at home and fields, and evening outdoor activities [ 21 , 47 , 62 64 ]. In Zanzibar, qualitative methods were used to explore night-time activities and sleeping patterns in one study while another study used a combination of survey research and structured observation to identify the variation in levels of net use [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Health studies found that people of Raglai ethnicity had a higher risk of malaria infection and malnutrition rates among children under 5 years of age in comparison to those who were of Kinh ethnicity [54,[58][59][60].…”
Section: Study Site and Populationmentioning
confidence: 99%